2015
DOI: 10.1186/s13018-015-0196-6
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a genetically modified muscle flap for local BMP-2 production and its effects on bone healing: a histomorphometric and radiological study in a rat model

Abstract: Aim of the studyWe developed an experimental rat model to explore the possibility of enhancing the healing of critical-size bone defects. The aim of this study was to demonstrate the feasibility of this concept by achieving high local BMP-2 expression via a transduced muscle flap that would facilitate bony union while minimizing systemic sequelae.MethodsThe transduction potential of the adenoviral vector encoding for BMP-2 was tested in different cell lines in vitro. In vivo experiments consisted of harvesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Moreover, studies such as Dempsey et al have demonstrated genetically modified free flaps can be used without eliciting toxic systemic effects, through delivering IL-12 directly into the local environment of a skin tumor and suppress its growth [ 74 ]. The remarkable strides in research in flap biology and tissue engineering are currently being heavily applied to tumor suppression, but numerous studies have proved these effects would translate seamlessly to anti-aging applications [ 75 – 79 ]. Nonetheless, genetic modification of flaps may pose risks of increased rejection among patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies such as Dempsey et al have demonstrated genetically modified free flaps can be used without eliciting toxic systemic effects, through delivering IL-12 directly into the local environment of a skin tumor and suppress its growth [ 74 ]. The remarkable strides in research in flap biology and tissue engineering are currently being heavily applied to tumor suppression, but numerous studies have proved these effects would translate seamlessly to anti-aging applications [ 75 – 79 ]. Nonetheless, genetic modification of flaps may pose risks of increased rejection among patients.…”
Section: Discussionmentioning
confidence: 99%